2013
DOI: 10.5430/ijhe.v2n3p62
|View full text |Cite
|
Sign up to set email alerts
|

Research on Revision of Training Program of the Economics and Management Specialties Based on the Training Mode--- A Case Study from Changchun University of Science and Technology

Abstract: With China's economic development and international competition intensifications, the society requires for talents from number requirements into the quality requirements, especially. Complex and high-class trend of modern industrial development demands compound talents. There are eight majors in college of the economics and management in Changchun University of Science and Technology, so it is an urgent for the university how to cultivate compound talents of high-quality. In September 2012, new "University und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In recent years, with the advancement of science and technology and the development of society, people are more and more interested in the research of artificial intelligence. Among them, the automatic recognition of expressions is a key part of the field of artificial intelligence, and it has attracted more and more attention [1]. However, due to the complexity and subtle changes in expression, the recognition of the same person's expression may be different due to changes in image illumination, image posture, gender, age, facial hair, and glasses worn.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the advancement of science and technology and the development of society, people are more and more interested in the research of artificial intelligence. Among them, the automatic recognition of expressions is a key part of the field of artificial intelligence, and it has attracted more and more attention [1]. However, due to the complexity and subtle changes in expression, the recognition of the same person's expression may be different due to changes in image illumination, image posture, gender, age, facial hair, and glasses worn.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the inherent limitations in the APF method [21], the approach in [22] added virtual target points to modify the force equilibrium at those specific locations. Reference [23] introduced random disturbance components into the attractive potential field. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Through the literature research, we found that the above methods can perform ear recognition, but compared with traditional ear recognition algorithms, the ear recognition algorithm based on deep learning has certain advantages [21]. In deep learning, the singlestage network is faster than the two-stage network.…”
Section: Introductionmentioning
confidence: 99%